2017
DOI: 10.1017/s1751731116001300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of advancing the supply of finisher diet on growth performances and carcass and pork quality of heavy barrows and gilts

Abstract: A total of 120 Duroc × (Large White × Landrace) pigs, 50% barrows and 50% gilts, with 54.1 ± 0.14 kg BW and 103 ± 3 days of age, were used to study the effect of advancing the shift to a standard finisher feed from 100 to 90 and 80 kg BW on production performances and carcass and pork quality. Each of the six treatments (two sexes × three BWs at time of feeding shift) was replicated four times and the experimental unit was the pen (with five pigs for growth performance and carcass variables and three pigs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These results imply that increasing the dietary energy in gilts destined for Teruel ham from 76 to 134 kg BW could compensate pig farmers, depending on the price of fat sources. Additionally, in this period and in these types of gilts, the application of a diet with low CP and AA contents would reduce feeding cost, because this diet is cheaper, without penalizing growth performance, as well as contributing to reduced nitrogen losses to the environment [30]. When the period of administration of the experimental diets was broader (around 30-115 kg BW), several authors [31][32][33] found no effect of increase dietary energy on ADG and ADFI.…”
Section: Growth Performancementioning
confidence: 99%
“…These results imply that increasing the dietary energy in gilts destined for Teruel ham from 76 to 134 kg BW could compensate pig farmers, depending on the price of fat sources. Additionally, in this period and in these types of gilts, the application of a diet with low CP and AA contents would reduce feeding cost, because this diet is cheaper, without penalizing growth performance, as well as contributing to reduced nitrogen losses to the environment [30]. When the period of administration of the experimental diets was broader (around 30-115 kg BW), several authors [31][32][33] found no effect of increase dietary energy on ADG and ADFI.…”
Section: Growth Performancementioning
confidence: 99%
“…Diet balancing was calculated on the basis of current recommendations for highly productive animals; it was regulated on the basis of age, sex, and live weight [15].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of studying the fatty acid composition is noted in many scientific studies [15][16][17][18]. Studies of the chemical composition and physical parameters of the pork fat are presented in table 7.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained with the experimental diets would imply that the increase in 0.15 Mcal of net energy/kg in the diet, from 80 to 137 kg BW, in barrows intended for Teruel dry-cured ham elaboration, could be beneficial for pig farmers, depending on the price of fat sources. In addition, in this period and in this type of animals, a reduction in 2% of CP and 0.10% of standardized ileal digestible lysine would decrease feeding costs, increase the profits of pig farmers and reduce nitrogen losses to the environment [31].…”
Section: Growth Performancementioning
confidence: 99%